1978
DOI: 10.1073/pnas.75.10.4694
|View full text |Cite
|
Sign up to set email alerts
|

Chemical determination of the m1 Moloney sarcoma virus pP60gag gene order: evidence for unique peptides in the carboxy terminus of the polyprotein.

Abstract: The gene order of the ml Moloney sarcoma virus (mMSV) specific pP60 gag (P60) was determined by direct chemical analysis of the polyprotein. P60 was cleaved with cyanogen bromide (CNBr) into eight partial and complete fragments ranging in mass from 10,000 daltons to 58,000 daltons. Peptide maps of these fragments were compared to maps of p15, p12, and three CNBr fragments of p30. (D. Bolognesi, personal communication). In these studies we show that the p30 of M-MuLV and m3MSV have comparable peptide maps an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1978
1978
1983
1983

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…A recent study by Oskarsson et al (34) demonstrated that the additional peptides in mlMSV p30 represent information derived from the COOH end of m1MSV p30. These mlMSV marker peptides are also evident in the mlMSV gag precursor polyprotein, p60, of p521 (34) and in the p30 and p60 of the noninfectious mlMSV particle produced by the sarcoma-positive leukemia-negative cell line D56 (35) (data not shown). The m3MSV p30 has been similarly tested and does not display the marker seen in mlMSV p30.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Oskarsson et al (34) demonstrated that the additional peptides in mlMSV p30 represent information derived from the COOH end of m1MSV p30. These mlMSV marker peptides are also evident in the mlMSV gag precursor polyprotein, p60, of p521 (34) and in the p30 and p60 of the noninfectious mlMSV particle produced by the sarcoma-positive leukemia-negative cell line D56 (35) (data not shown). The m3MSV p30 has been similarly tested and does not display the marker seen in mlMSV p30.…”
Section: Resultsmentioning
confidence: 99%
“…The m3MSV contains a p70 gag precursor and a p30 that migrates slightly slower than mlMSV p30 in sodium dodecyl sulfate/ polyacrylamide gel electrophoresis. Both ml and m3MSV lack plO (34), presumably due to inclusion of this portion of the Moloney MuLV genome (adjacent to the COOH end of p30) in the src-associated deletion-substitution that generated the two MSVs. This suggests that ml but not m3MSV p30 was affected by the swc-associated deletion-substitution.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we have studied two variants of the defective transforming Moloney murine sarcoma virus (MuSV) called ml (1)(2)(3) and (4). Although these variants were originally derived from a tumor-inducing uncloned MuSV stock (5), they have been maintained separately for more than 10 years in different hosts and cells.…”
Section: Introductionmentioning
confidence: 99%
“…We (8). Tryptic peptide analysis of the mlMSV p60 indicated the presence of an as yet unidentified peptide (<20,000 Mr) at the COOH terminal of the molecule (9). Antisera to the mlMSV p60 have been raised to protein purified from the mlMSV(FeLV) pseudotype (2).…”
mentioning
confidence: 99%